2017
DOI: 10.1523/jneurosci.2281-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Stressors Facilitates Long-Term Synaptic Potentiation in the Lateral Habenula

Abstract: The lateral habenula (LHb) is a small part of the epithalamus that projects to monoamine centers in the brain. Previously, neurotransmission onto the LHb was shown to be abnormally potentiated in animal models of depression. However, synaptic plasticity in this brain area and the effect of stressor exposure on synaptic plasticity of the LHb have not been investigated. Thus, we explored whether the LHb undergoes dynamic changes in synaptic efficacy or not. First, we observed that a moderate LTP occurs in a frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 56 publications
4
39
0
Order By: Relevance
“…Surprisingly, a single exposure to restraint plus tail shock (RTS) selectively prevented LFS-LTD and mGluR-LTD induction while leaving a 13-Hz-induced LTD (MFS-LTD) intact. Together with our previous report (Park et al, 2017), our results show that the LHb exhibits bidirectional synaptic plasticity and that acute stress can greatly disrupt the balance between LTP and LTD in the LHb, shifting to further potentiation of LHb activity.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Surprisingly, a single exposure to restraint plus tail shock (RTS) selectively prevented LFS-LTD and mGluR-LTD induction while leaving a 13-Hz-induced LTD (MFS-LTD) intact. Together with our previous report (Park et al, 2017), our results show that the LHb exhibits bidirectional synaptic plasticity and that acute stress can greatly disrupt the balance between LTP and LTD in the LHb, shifting to further potentiation of LHb activity.…”
Section: Introductionsupporting
confidence: 88%
“…Prolonged MFS also induced LTD in the LHb. We recently showed that mild LTP also can occur in the LHb upon theta burst stimulation, although the magnitude of potentiation was smaller compared to that observed in other structures, including the hippocampus (Park et al, 2017). These findings implicate that the LHb exhibits bidirectional synaptic plasticity, although the efficacy for potentiation and that for depression do not seem to be equally balanced in the LHb.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A tight causal relationship of P2X7Rs with mood disorders is imperatively suggested by their involvement in neuroinflammation and the subsequent modulation/damage of neuronal circuits in mood-relevant areas of the brain. Functional changes in long-term synaptic potentiation (LTP) in the lateral habenula have been observed in rats exposed to inescapable stressors leading to learned helplessness (Li et al, 2011;Park et al, 2017). Similarly, in models of learned helplessness, the expression of synapse-related genes decreased, indicating the loss of synaptic structures.…”
Section: Discussionmentioning
confidence: 99%